Diabetes in the elderly. (February 2019) - Abdelhafiz, Ahmed H.; Sinclair, Alan J.
Abstract: The prevalence of diabetes mellitus is increasing, and its epidemiology is shifting towards old age because of increased life expectancies. As a result, diabetes mellitus is increasingly becoming a disease of older rather than middle age. The increased prevalence of co-morbidities associated with ageing, combined with the increased prevalence of geriatric syndromes that lead to physical and mental disabilities, contributes to the complexity of managing diabetes in the elderly. Taking into account the heterogeneous functional status, co-morbidities and life expectancy of older people, therapeutic interventions and glycaemic targets should be individualized, considering patients' preferences and putting quality of life at the heart of their care plans.